ФРАЗЕОЛОГИЗМЛЕР – ӘҲМИЙЕТЛИ ЛИНГВОПОЭТИКАЛЫҚ ҚУРАЛ - Ержанова, Д.Қ. (FAN va JAMIYAT, 2023)
The linguopoetic features of phrasems in the works of Ibrayim Yusupov are illustrated in the given article. The analyses of specific changes in their semantic structures are given through examples.